Risk, education and child labour in Indonesia - Emla Fitzsimons (Institute for Fiscal Studies (IFS), 2002)
We study the effects of risk and uncertainty on education in Indonesia. Households that face more uncertainty, and that have limited or no access to formal insurance, will have a higher motive for self-insurance and this may have adverse consequences for investment in child education. A key contribution of the paper is to decompose risk into village- and household-level components, and to estimate whether they have different effects on education. We find no evidence of household risk affecting child education, however there is evidence that village risk adversely affects investment in education.
Keywords: 330; Kinderarbeit; Indonesien